EAT ME : Trapholt. - Grøn, Karen; Westergaard, Vera (Kolding : Trapholt, 2017)
Bannino, Dan ; Brühl, Simone ; Dahlgaard, Søren ; Evaristti, Marco ; Lucas, Sarah ; Nielsen, Hanne ; Raeven, L. A. ; Suriraja, Liu ; Willing, Elizabeth ; Wurn, Erwin ; Chadwick, Helen ; Edvard, Jonas ; Velthuis, Tomm ; Westphal, Uli ; Dobriban, Arpad ; Isaacs, John ; Sterbak, Jana ; Tsykalov, Dimitri ; Brocard, Charlotte ; Bjørn, Katja ; Gallaccio, Anya ; Jeon, Jinjyun ; Lyngsholm, Trine ; Löwén, Jette ; Vogelzang, Marije ; Eken, Rose ; Franke, Anja ; Honey & Bunny ; Mingwei, Lee ; Simon, Taryn ; Ourasanah, Mansour ; Rutzerveld, Chloé ; Next Nature Network ; Harrison, Ellie ; Miralda, Antoni ; Nyholm, Johannes ; Rentmeister, Thomas ; SUPERFLEX ; SWAMP ; Three
EAT ME, Trapholt, Kolding, september 2017 - maj 2018
boek